2004
DOI: 10.1158/1078-0432.ccr-03-0721
|View full text |Cite
|
Sign up to set email alerts
|

Combined Histopathological and Molecular Cytogenetic Stratification of Medulloblastoma Patients

Abstract: This study examined the utility of stratifying children with medulloblastomas by a combination of refined histopathological classification and molecular cytogenetic evaluation.Detailed histopathological classification of tumors from a cohort of patients (n ‫؍‬ 87) composed mainly of children entered into the International Society of Pediatric Oncology (SIOP)/United Kingdom Children's Cancer Study Group PNET3 trial (n ‫؍‬ 65), included identification of the large cell/anaplastic phenotype. Fluorescence in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
152
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(167 citation statements)
references
References 36 publications
11
152
1
3
Order By: Relevance
“…MYCN ampliWcation is a hallmark of tumors with poor clinical outcome [13,19]. Intriguingly, two MB showed unexpected loss of cells bearing MYCN ampliWcation within their intracranial metastatic deposits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MYCN ampliWcation is a hallmark of tumors with poor clinical outcome [13,19]. Intriguingly, two MB showed unexpected loss of cells bearing MYCN ampliWcation within their intracranial metastatic deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical staging systems based on age, metastatic stage at diagnosis and, in some studies, extent of surgical resection have so far been the most useful methods for the stratiWcation of patients into standard and high risk therapy groups [1,26,27]. Additionally, after reWnement of the histological classiWcation of MB in the 2007 WHO classiWcation, the histological subtype is of potential prognostic relevance: large cell/anaplastic MB behaves more aggressively, while nodular/ desmoplastic variants show a more favorable clinical course as compared to the large group of classic MB [3,5,7,10,13,14,17]. Some recent studies have extended the concept of anaplasia in MB and suggested that this phenomenon reXects malignant progression of a tumor and may occur in various MB subtypes independent of large cell histology [3,4,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some CCAs have also been proposed as independent prognostic markers and determinants of new MB subtypes (Lamont et al 2004;Gilbertson and Ellison 2008;McCabe et al 2011). Here, we identified many numerical and structural alterations in both cell lines evaluated, mainly chromosomal gain and structural rearrangement of chromosome 1 and 7.…”
Section: Discussionmentioning
confidence: 83%
“…Some recurrent chromosomal changes have been recently reported to predict survival in MB patients including loss of 17p (Batra et al 1995;Lamont et al 2004), gain of 17q (Pfister et al 2009), presence of an isodicentric chromosome 17 (idic(17)(p11.2)) (Lamont et al 2004;Pan et al 2005), gain of 1q (Lo et al 2007) and monosomy 6 (Thompson et al 2006).…”
Section: Introductionmentioning
confidence: 99%